The efficiency of ethyl alcohol 70%, sodium hypochlorite 5.25%, zephiran chloride 1 1000 on gutta percha points disinfection - Fok, Tony; Kwa, Katherine; Jimena, Edna (Adviser)+.
The purpose of this study is: Firstly, to evaluate the antibacterial efficiency of three commonly available disinfectants, namely - Ethyl alcohol 70%, sodium hypochlorite 5.25%, Zephiran chloride 1.1000: secondly, to determine which of these disinfection offer the most rapid yet efficient disinfection of gutta percha points: and lastly, to know what specific microbes are affected by these different disinfectants.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.